Comparing rewarding and reinforcing properties between 'bath salt' 3, 4‐methylenedioxypyrovalerone (MDPV) and cocaine using ultrasonic vocalizations in rats. (1st December 2016) - Simmons, Steven J.; Gregg, Ryan A.; Tran, Fionya H.; Mo, Lili; von Weltin, Eva; Barker, David J.; Gentile, Taylor A.; Watterson, Lucas R.; Rawls, Scott M.; Muschamp, John W.
Abstract: Abuse of synthetic psychostimulants like synthetic cathinones has risen in recent years. 3, 4‐Methylenedioxypyrovalerone (MDPV) is one such synthetic cathinone that demonstrates a mechanism of action similar to cocaine. Compared to cocaine, MDPV is more potent at blocking dopamine and norepinephrine reuptake and is readily self‐administered by rodents. The present study compared the rewarding and reinforcing properties of MDPV and cocaine using systemic injection dose‐response and self‐administration models. Fifty kilohertz ultrasonic vocalizations (USVs) were recorded as an index of positive affect throughout experiments. In Experiment 1, MDPV and cocaine dose‐dependently elicited 50‐kHz USVs upon systemic injection, but MDPV increased USVs at greater rates and with greater persistence relative to cocaine. In Experiment 2, latency to begin MDPV self‐administration was shorter than latency to begin cocaine self‐administration, and self‐administered MDPV elicited greater and more persistent rates of 50‐kHz USVs versus cocaine. MDPV‐elicited 50‐kHz USVs were sustained over the course of drug load‐up whereas cocaine‐elicited USVs waned following initial infusions. Notably, we observed a robust presence of context‐elicited 50‐kHz USVs from both MDPV and cocaine self‐administering rats. Collectively, these data suggest that MDPV has powerfully rewarding and reinforcing effects relative to cocaine at one‐tenth doses. Consistent with prior work, we additionally interpret these data in supporting that MDPV has significant abuse risk based on its potency and subjectively positive effects. Future studies will be needed to better refine therapeutic strategies targeted at reducing the rewarding effects of cathinone analogs in efforts to ultimately reduce abuse liability. Abstract : Our work shows that the synthetic cathinone 3, 4‐methylenedioxypyrovalerone evokes sustained rewarding effects (assessed via 50‐kHz ultrasonic vocalizations) in systemic dose‐response and self‐administration models compared with cocaine. Results extend growing literature on abuse liability associated with novel psychoactive substances including cathinone analogs. Future work should identify neuronal circuits governing positive subjective effects of 3, 4‐methylenedioxypyrovalerone that in turn direct drug‐seeking behavior.